Analisis Hukum Kasus Penembakan Pendeta Yeremia Zanambani dalam Perspektif Hak Asasi Manusia - Raden Andante; Kharisma Hafids Wirabrata (Syntax Corporation Indonesia, 2024)
This research aims to analyze in depth the shooting case of Pastor Jeremiah Zanambani from the perspective of law and human rights. In addition, the paper will also discuss the challenges in law enforcement in conflict areas, the social, political, and legal impacts of the shooting cases and provide policy recommendations to prevent the recurrence of state violence cases in the future. The research methods used in the legal analysis of the shooting case of Pastor Jeremiah Zanambani in a human rights perspective can include several key steps. First, the researcher will conduct a detailed case study related to the chronology of events, relevant facts, and social and political context in Papua. The social, political, and legal impact of the shooting of Pastor Jeremiah Zanambani is complex and multifaceted. From public trauma and mistrust, to rising political tensions, to major challenges in law enforcement, all of these aspects show the urgency of the need for reforms and new approaches to dealing with conflict in Papua.